2013
DOI: 10.1016/j.jtbi.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for neutral speciation via isolation by distance

Abstract: The branching of new species from an ancestral population requires the evolution of reproductive isolation between groups of individuals. Geographic separation of sub-populations by natural barriers, if sustained for sufficiently long times, may lead to the accumulation of independent genetic changes in each group and to mating incompatibilities (Mayr, 2001; Fitzpatrick et al., 2009). A similar phenomenon may occur in the absence of barriers via isolation by distance if the population is distributed over large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…For one thing, this is a contradiction in terms: invariability of a specific phenotype leaves nothing on which selection can act. Although never explicitly stated by lichenologists, evolution without phenotypic divergence would require an alternative to speciation through natural selection or imply neutral speciation (Baptestini et al 2013). Neutral speciation in lichenized fungi is a conceivable possibility but is unlikely to be common due to widespread sympatry, and would be difficult to prove.…”
Section: Small Thalli Are Small Canvasses For Exhibition Of Phenotypementioning
confidence: 99%
“…For one thing, this is a contradiction in terms: invariability of a specific phenotype leaves nothing on which selection can act. Although never explicitly stated by lichenologists, evolution without phenotypic divergence would require an alternative to speciation through natural selection or imply neutral speciation (Baptestini et al 2013). Neutral speciation in lichenized fungi is a conceivable possibility but is unlikely to be common due to widespread sympatry, and would be difficult to prove.…”
Section: Small Thalli Are Small Canvasses For Exhibition Of Phenotypementioning
confidence: 99%
“…Individuals reproduce sexually in a mating range and the species definition is based on reproductive isolation. Genetic diversity, generated by recombination and mutation, correlates with the spatial dimension (of mating range) (Baptestini et al , b, Martins et al ). As a result, individuals that are far apart tend to be genetically different, forming species in spatial clusters of genetically similar individuals (de Aguiar et al , Baptestini et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity, generated by recombination and mutation, correlates with the spatial dimension (of mating range) (Baptestini et al , b, Martins et al ). As a result, individuals that are far apart tend to be genetically different, forming species in spatial clusters of genetically similar individuals (de Aguiar et al , Baptestini et al ). Previous results using the same modelling framework (Costa et al ) have shown that the mating range significantly affects the branching tempo: larger mating ranges (when individuals use the same geographic region, corresponding to sympatry) lead to an increase in the rate of speciation throughout the radiation process.…”
Section: Introductionmentioning
confidence: 99%
“…Population fragmentation is characterized by critical changes in the spatial distribution of individuals, creating isolated subgroups of a given initial population. This phenomenon has important consequences for secondary processes such as epidemic spreading, species invasion [1], or also speciation [2]. Fragmentation is often attributed to landscape heterogeneity, which encompasses the spatial distribution of geographic and environmental features [3].…”
Section: Introductionmentioning
confidence: 99%